Incorporating spirit. (22nd December 2017) - Stone, Emma Francis
Abstract : The barrier that separates the spiritual and earthly worlds is paper thin in Brazil. The infusion of the spiritual into the secular manifests in diverse ways, but is perhaps best represented by the prevalence of ritual possession in the region, where the spiritual and material merge. This paper will focus on the phenomenon of ritual possession within Umbanda, an eclectic Afro-Brazilian spiritual tradition. It will first explore existing sociological and socio-functionalist analyses or ritual possession in Brazil, and then argue that there is a need for an analysis that makes sense of possession from an embodied perspective. Drawing on the testimonies of mediums from two Umbanda centers in Rio de Janeiro (the Casa da Caridade Caboclo Peri) and Sao Paulo (Templo Guaracy) in Brazil, the article will investigate the appeal of ritual possession as a spiritual practice located and experienced in the body.